Vascular Malformations: A Review - Cox, Joshua A.; Bartlett, Erica; Lee, Edward I. (Seminars in Plastic Surgery, 2014)
Identification and treatment of vascular malformations is a challenging endeavor for physicians, especially given the great concern and anxiety created for patients and their families. The goal of this article is to provide a review of vascular malformations, organized by subtype, including capillary, venous, lymphatic and arteriovenous malformations. Only by developing a clear understanding of the clinical aspects, diagnostic tools, imaging modalities, and options for intervention will appropriate care be provided and results maximized.
Keywords: vascular malformation; capillary malformation; venous malformation; lymphatic malformation; arteriovenous malformation